Quality Management Approaches in Academic Libraries: A Pilot Study of a Nigerian University Library - Egberongbe, Halima; Sen, Barbara; Willett, Peter (Qualitative and Quantitative Methods in Libraries, 2017)
The paper reports the findings of a pilot case study in a university library in South-West Nigeria.  The study was carried out to investigate the library’s quality management approaches and which formed part of a larger project to recommend a common model of quality management for academic libraries in this region.  The study involved a semi-structured interview with the university librarian, a focus group involving lower management staff, and documentary analysis.  It was found that while the concepts of quality and of quality management were generally understood, there were obvious problems in areas such as customer service and performance measurement.